Structural Engineering of Multilayer TiN / CrN System Obtained by the Vacuum Arc Evaporation - O.V. Sobol’; A.A. Andreev; V.A. Stolbovoy; V.F. Gorban’; N.V. Pinchuk; A.A. Meylekhov (Журнал нано- та електронної фізики)
By the X-ray diffraction, electron microscopy, and microindentation methods we have investigated the phase composition, structure, substructure and hardness of vacuum arc multilayer coatings of TiN / CrN system obtained in the range of nitrogen pressure of 1×10–5 ... 5×10–3 Torr when applying continuous and pulsed negative bias potential. Formation of two-phase state with a preferred orientation of the crystallite growth was established at high pressure of (1 ... 5)×10–3 Torr and feeding of negative DC bias potential: Ub = – 20 V – texture axis [100], at – 230 V – texture axis [111]. Based on the studies of substructural state, connection of the transition to the superhard (57 GPa) state with decrease in the crystallite size and microstrain in TiN layers was established.